SIMULASI KENYAMANAN TERMAL MODEL REKOMENDASI TAMAN AIR BERARSITEKTUR TRADISIONAL BALI PADA TAMAN KOTA I GUSTI NGURAH MADE AGUNG DI DENPASAR - I Wayan Wirya Sastrawan; I Gede Surya Darmawan (Universitas Dwijendra, 2018)
People will always try to condition his environment to achieve thermal comfort for his body. To conditioning the external environment is strongly influenced by climatic conditions. In other words, the comfort that humans feel in the outer space is depend on the thermal conditions of the environment. The object of outer space in this research is the built environment with the shape of Taman Kota I Gusti Ngurah Agung in Denpasar City. City Park as the object of research so far only judged from its function as a convenient recreational facility for the city community, both from the visual comfort and the thermal comfort. To answer the needs of thermal comfort in the city park, the focus of this research is the conditioning of the outer space elements with the concept of Balinese Traditional Architecture to improve the thermal comfort of the esksisting conditions. The purpose of this research is to produce thermal comfort optimization of city park through recommendation of arrangement model with the concept of Water Garden of Traditional Architecture of Bali. It takes thermal condition visualization using Envi-MET 3.1 software to see thermal enhancement improvement in the research object recommendation model. The result of this research is mapping of the increase of thermal comfort quantity distribution at the condition of urban park recommendation model. From the mapping of the thermal conditions, it is known that the thermal comfort level of the urban park recommendation model is higher. This result can then be followed up as a recommendation model of Taman Kota I Gusti Ngurah Made Agung with the concept of Water Garden of Traditional Architecture of Bali and the future can be applied in other cities with similar characteristics.